Blockchain Technology in Digital Marketing: Roles and Challenges - Pahlawan, Princhita Nabila Maram (International Journal of Economics, Business, and Entrepreneurship, 2022)
Implementation of Blockchain Technology (BCT) has an important effect on digital marketing to increase the company sales, and develop the customers’ trust, but theimplementation of Blockchain technology in dealing with Digital Marketing is still limited. Therefore, the purpose of this article is to explore how important the role of BCTimplementation in Digital marketing is and how its challengesare faced. The results show that not all companies have implemented Blockchain Technology for marketing activity, especially in dealing with Digital Marketing Implementation.The handicaps that companies did not implement Blockchain Technology are in terms of low technology literacy of human capital and technology infrastructure availability due to thelimited investment capital. So, these are the challenges for the company especially in SMEs to have human capital with high technology literacy and skills or talents, and require full system of digital technology infrastructure supported by the government role. Masukkan has